Vernacular Architecture of a Rural Magar Settlement of Nepal: The Case of Taka, Putha Uttarganga Rural Municipality, East Rukum - Pant, Mohan Moorti; Suwal, Ram Prasad; Maharjan, Sampurna; Awale, Orna; Shrestha, Rajan; Lakha, Punam (Far Western Review, 2023)
The vernacular settlement of the Magar community in the Taka village of East Rukum are still lively, and represent the society, cultural and history of the place, which reflects the sustainable living pattern of a rural community. This study of Taka village clearly defines the geography, settlement pattern, community groups, settlement cluster, social structure, construction of dwelling and rituals. It further identifies the dwelling types and construction technology on the basis of three features: i. representation of each community, ii. Representation of each locality, and iii. Representation of variation in house form. The settlement pattern and dwelling form in a way represent the characteristics of social structure and life style in the sharing of spaces of the dwelling environment. The dwelling form, building materials and construction technology blends with the terrain profile and climate creating a harmonious settlement pattern with nature and society. There is also community awareness on the conservation of Taka rural settlement heritage which is the positive sign on maintaining the identity of the community and place.